Muse of fire : reflections on theatre - McNally, Terrence (Fairleigh Dickinson University Press ; copublished by The Rowman & Littlefield Publishing Group, Inc., 2021)
"Muse of Fire is a collection of the four-time Tony Award-winning playwright's meditations on the power of theater to change minds by first changing hearts, and on the responsibilities of the playwright as a member of the theater community"--